2013
DOI: 10.1080/01932691.2013.774282
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Aqueous Solutions Containing SLES, CAPB, and Microemulsion: Influence of Cosurfactant and Salt

Abstract: Aqueous solutions containing sodium lauryl ether sulphate (SLES) and cocamidopropyl Betaine (CAPB) with a constant total surfactant concentration (10 wt%) but different volume mixing ratios were prepared. A remarkable increase in the solutions' viscosity at a volume mixing ratio of 34 v/v% SLES to 66 v/v% CAPB was observed. By increasing the volume ratio of SLES (r-value) in the binary mixture, the viscosity of 10 wt% SLES, which is close to that of water, increases to a maximum, but then drops down drasticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Previous scattering studies of SLES/CAPB systems indicate persistence lengths of 600 Å, for dilute (0.2 wt %) WLMs in 3–5 wt % electrolyte and with relatively large uncertainties in modeled contour lengths (±900 – 10,000 Å) . Rheological studies identified a sharp peak in the zero-shear viscosity for 10 wt % SLES/CAPB with a mass ratio of 34:66 without the electrolyte, indicative of a wormlike transition . The addition of electrolyte promotes the formation of WLMs at lower surfactant concentrations, and above a critical electrolyte concentration, semidilute solutions form a branched network that exhibits a significantly reduced viscosity .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous scattering studies of SLES/CAPB systems indicate persistence lengths of 600 Å, for dilute (0.2 wt %) WLMs in 3–5 wt % electrolyte and with relatively large uncertainties in modeled contour lengths (±900 – 10,000 Å) . Rheological studies identified a sharp peak in the zero-shear viscosity for 10 wt % SLES/CAPB with a mass ratio of 34:66 without the electrolyte, indicative of a wormlike transition . The addition of electrolyte promotes the formation of WLMs at lower surfactant concentrations, and above a critical electrolyte concentration, semidilute solutions form a branched network that exhibits a significantly reduced viscosity .…”
Section: Introductionmentioning
confidence: 94%
“…Rheological studies identified a sharp peak in the zero-shear viscosity for 10 wt % SLES/CAPB with a mass ratio of 34:66 without the electrolyte, indicative of a wormlike transition . The addition of electrolyte promotes the formation of WLMs at lower surfactant concentrations, and above a critical electrolyte concentration, semidilute solutions form a branched network that exhibits a significantly reduced viscosity . Above the dilute surfactant regime, the low- q scattering gradient flattens with increasing surfactant concentration due to the additional inter-worm volume exclusion …”
Section: Introductionmentioning
confidence: 99%
“…WLM form at lower salt concentrations. 50 To ensure the validity of our CAPB model, a simulated salt curve for SLES 1 EO:CAPB at 11wt%, ratio 9.85 to 1.15 wt%, was generated, as in the work of Tang et al 34 All simulations for the salt curve were performed in NVT ensemble using DL MESO mesoscale simulation package 51 and all the systems were simulated in a cubic box with volume of 64 × 10 3 DPD unit length. Slater-type charge smearing was applied to the systems, as in previous works.…”
Section: Effect Of Co-surfactantmentioning
confidence: 99%
“…Although the SLES–CapB surfactant system is extensively used for its rheological properties, there are not a lot of studies that characterize its rheology and microstructure [18–21]. Mitrinova et al .…”
Section: Introductionmentioning
confidence: 99%